ANALYSIS OF THE EFFECTIVENESS OF RAILWAY SERVICE IN LAMPUNG ON THE TANJUNG KARANG STATION – KOTABUMI STATION ROUTE - Muhamad Choirudin K; Aleksander Purba; Rahayu Sulistyorini; Muhammad Karami; Mohd Isneini (RADJA PUBLIKA, 2026)
This study aims to analyze the effectiveness of railway services in Lampung on the Tanjung Karang–Kotabumi route from the users’ perspective using a quantitative survey-based approach. The research focuses on Rajabasa (economy class) and Kuala Stabas (premium class) train services. Data were collected through Likert-scale questionnaires and secondary sources using an accidental simple random sampling technique. The variables include traveler characteristics, travel characteristics, and transportation system facilities. Data validity and reliability were tested before being analyzed using the Classification and Regression Tree (CART) method. The results indicate that service effectiveness is strongly influenced by the quality of interaction between staff and passengers as well as the condition of physical carriage facilities. Staff attributes emerge as the most dominant factor with the highest satisfaction scores, while management aspects remain the primary weakness. Differences in facility quality between premium and economy classes and accessibility issues in premium services were also identified. The CART model reveals that integrated operational and service quality is the key determinant, with staff attributes as the strongest predictor. The optimal model was obtained at a 1.5 threshold with high accuracy.